Identification of Recycled Cooking Oil By Varying Number of Au/GO Coated Fiber Optic’s Loop Ring - Wan Maisarah Mukhtar; Nur Fatin Liyana Manaf; Razman Mohd Halim (Academy of Sciences Malaysia, 2024)
Indexed by SCOPUS/MYCITE